2017
DOI: 10.1038/s41598-017-03873-9
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Levels of Reactive Oxygen Species Coordinate Metabolic Activity with Beta-cell Mass Plasticity

Abstract: The pancreatic beta-cells control glucose homeostasis by secreting insulin in response to nutrient intake. The number of beta-cells is under tight metabolic control, as this number increases with higher nutrient intake. However, the signaling pathways matching nutrition with beta-cell mass plasticity remain poorly defined. By applying pharmacological and genetic manipulations, we show that reactive oxygen species (ROS) regulate dose-dependently beta-cell proliferation in vivo and in vitro. In particular, reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 44 publications
0
27
0
Order By: Relevance
“…In turn, manipulations leading to decreases in cellular ROS levels prevented normal β-cell differentiation. Moderate increases in cytosolic H 2 O 2 were found to promote β-cell proliferation in zebrafish, whereas high H 2 O 2 levels can stimulate differentiation of new β-cells from progenitors (8). It has been hypothesized that the moderate H 2 O 2 levels are necessary for β-cell proliferation.…”
Section: Impaired Biogenesis Of Pancreatic β-Cellsmentioning
confidence: 99%
“…In turn, manipulations leading to decreases in cellular ROS levels prevented normal β-cell differentiation. Moderate increases in cytosolic H 2 O 2 were found to promote β-cell proliferation in zebrafish, whereas high H 2 O 2 levels can stimulate differentiation of new β-cells from progenitors (8). It has been hypothesized that the moderate H 2 O 2 levels are necessary for β-cell proliferation.…”
Section: Impaired Biogenesis Of Pancreatic β-Cellsmentioning
confidence: 99%
“…Interestingly, ROS is known to increase apoptosis and in high concentrations induce cell cycle arrest. However, in low to moderate concentrations, ROS have been found to stimulate cell proliferation (Boonstra and Post, 2004; Ahmed Alfar et al, 2017). In addition, experimental studies have shown that mitochondrial ROS play an important role in beta-cell proliferation (Ahmed Alfar et al, 2017) and in the establishment of beta-cell mass during development (Zeng et al, 2017).…”
Section: Adaptive Changes Of Beta-cell Mass In Obesity and Type 2 Diamentioning
confidence: 99%
“…However, in low to moderate concentrations, ROS have been found to stimulate cell proliferation (Boonstra and Post, 2004; Ahmed Alfar et al, 2017). In addition, experimental studies have shown that mitochondrial ROS play an important role in beta-cell proliferation (Ahmed Alfar et al, 2017) and in the establishment of beta-cell mass during development (Zeng et al, 2017). The loss of beta-cell mass in T2D can be explained by the increased apoptosis rate observed in islets from T2D patients (Butler et al, 2003; Rahier et al, 2008; Hanley et al, 2010) and the lack of increased beta-cell proliferation (Butler et al, 2003).…”
Section: Adaptive Changes Of Beta-cell Mass In Obesity and Type 2 Diamentioning
confidence: 99%
“…Inhibiting islet inflammation has emerged as an important objective for the protection of β-cells (Campbell-Thompson et al, 2016; Eizirik et al, 2009; Nordmann et al, 2017). It has been suggested that hyperglycemia in T2DM enhances the metabolic load on β-cells, causing an increase in the production of reactive oxygen species (ROS), in part, due to the oxidative nature of insulin protein folding and glucose metabolism (Ahmed Alfar et al, 2017). β-cell oxidative stress could promote inflammasome and caspase-1 activation, which can lead to the production and release of low levels of mature interleukin-1β (IL-1β).…”
Section: Introductionmentioning
confidence: 99%